DEPRESI PADA IBU-IBU YANG MEMPUNYAI ANAK CACAT YANG BERSEKOLAH DI YAYASAN PEMBINAAN ANAK CACAT (YPAC) MANADO - Munayang, Herdy; Kandou, L. F.J.; Rampengan, Novie; Sumarauw, Melisa E. (UNIVERSITAS SAM RATULANGI, 2012)
Abstract: According to data from the WHO, depression is still a serious public health problem. Depression is a disorder of human function related to feelings of sadness and its accompanying symptoms including alterations of sleep, appetite, psychomotor, concentration, anhedonia, and fatigue patterns. This study aimed to obtain degrees of depression by using the Hamilton Depression Rating Scale (HDRS) among mothers of disabled children who were studying at the Center for Disabled Children (YPAC) Manado. This was a descriptive study with a cross sectional design. There were 35 samples meeting the inclusion criteria. The results showed that by using the HDRS there were seven respondents (20%) showing normal personality and 28 respondents (80%) suffering from depression, mostly between the ages of 29-45 years (62.85%). From samples suffering from depression, there were 20 respondents (71.4%) with mild depression, seven (25%) with moderate depression, and one with severe depression (3.6%). Conclusion: A high number of mothers, especially at the ages of 29-45 years, of disabled children who were studying at YPAC Manado showed several degrees of depression. Among the depressed mothers, most suffered from mild depression. Keywords: mother, depression, disabled children, Hamilton Depression Rating Scale (HDRS). Abstrak: Menurut data WHO, depresi masih merupakan masalah kesehatan dunia yang serius. Depresi adalah terganggunya fungsi manusia yang berkaitan dengan alam perasaan sedih dan gejala penyertanya, termasuk perubahan pola tidur, nafsu makan, psikomotor, konsentrasi, anhedonia, dan kelelahan. Penelitian ini bertujuan untuk mendapatkan angka kejadian dan tingkat depresi dengan menggunakan Hamilton Depression Rating Scale (HDRS) pada para ibu yang memiliki anak cacat yang bersekolah di Yayasan Pembinaan Anak Cacat (YPAC) Manado. Penelitian ini bersifat deskriptif dengan menggunakan metode potong lintang. Sampel yang memenuhi kriteria inklusi berjumlah 35 orang. Hasil penelitian memperlihatkan bahwa dengan menggunakan Hamilton Depression Rating Scale (HDRS) terdapat tujuh responden berkepribadian normal dan 28 responden dengan depresi berbagai tingkat, terutama pada usia 29-45 tahun. Depresi ringan ditemukan sebesar 71,4%, depresi sedang 25%, dan depresi berat 3,6%. Simpulan: Sebagian besar ibu yang memiliki anak cacat yang bersekolah di YPAC Manado mengalami depresi, terutama depresi ringan. Kata kunci: ibu, depresi, anak cacat, Hamilton Depression Rating Scale (HDRS).